PENGARUH VARIABEL MAKRO EKONOMI TERHADAP KEMISKINAN DI KABUPATEN/KOTA PROVINSI ACEH - Muttaqien Muttaqien; M. Lutfi Al Fahmi; Neni Triana; Januar Fadli; Bobby Rahman (ITB AAS INDONESIA Surakarta, 2021)
The purpose of this study is to analyze macroeconomic variables, namely the human development index (HDI), unemployment and economic growth that have an impact on poverty levels in the District/City of Aceh Province. The data used in this study is time series data with a time period of 2015-2015. 2019 and cross-sectional data sourced from 23 regencies/cities in Aceh Province. The analytical method used in this study is panel data regression using the Eviews 10 analysis tool. The panel data regression estimation technique uses the Common Effect Model, Fixed Effect Model (FEM), and Random Effect Model (REM). Based on the results of the Chow test which analyzes The Common Effect and Fixed Effect Model are not in accordance with this study, then proceed with the Random Effect Model and continue with the Hausman test whose results show that the Random Effect Model is in accordance with this study. The results showed that HDI had no effect on poverty, while economic growth and unemployment had a significant and positive effect on poverty, then together the variables HDI, economic growth and unemployment had a significant and positive effect on poverty. Keywords: IPM, Unemployment, Economic Growth, Poverty